2004
DOI: 10.1086/423023
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experiments on Rotation and Alignment of the Analogs of Interstellar Dust Grains by Radiation

Abstract: The processes and mechanisms involved in the rotation and alignment of interstellar dust grains have been of great interest in astrophysics ever since the surprising discovery of the polarization of starlight more than half a century ago. Numerous theories, detailed mathematical models, and numerical studies of grain rotation and alignment with respect to the Galactic magnetic field have been presented in the literature. In particular, the subject of grain rotation and alignment by radiative torques has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 44 publications
(66 reference statements)
2
38
0
Order By: Relevance
“…For the dust species and interplanetary medium conditions considered Mukai and Schwehm find that the dust particles suffer only moderate erosion by sputtering before reaching the dust sublimation zone (see Section 5.2.5 related laboratory studies). Dust near the Sun can also be destroyed by rotational bursting (Misconi 1993, Abbas 2004). The dust PR effect varies and is enhanced during coronal mass ejections (Ragot and Kahler 2003).…”
Section: Dust Destruction and Dust Interactionsmentioning
confidence: 99%
“…For the dust species and interplanetary medium conditions considered Mukai and Schwehm find that the dust particles suffer only moderate erosion by sputtering before reaching the dust sublimation zone (see Section 5.2.5 related laboratory studies). Dust near the Sun can also be destroyed by rotational bursting (Misconi 1993, Abbas 2004). The dust PR effect varies and is enhanced during coronal mass ejections (Ragot and Kahler 2003).…”
Section: Dust Destruction and Dust Interactionsmentioning
confidence: 99%
“…In outer parts of the coma and in the tail, the alignment via radiative torques and interaction with solar wind could be important. For the comet environment the most important are mechanical alignment of grains rotating thermally (Gold, 1952;Purcell, 1979;Dolginov and Mytrophanov, 1976;Lazarian, 1994Lazarian, , 1997aLazarian, ,1997bRoberge et al, 1995) and suprathermally (Lazarian, 1995;Lazarian et al, 1996;Lazarian and Draine, 1997;Lazarian and Efroimsky, 1999) and radiative torque alignment (Dolginov, 1972;Dolginov and Mytrophanov, 1976;Weingartner, 1996, 1997;Weingartner and Draine, 2003;Abbas et al, 2004;Cho and Lazarian, 2005). For the review of the mechanisms of grain alignment see Lazarian ( 2003).…”
Section: Scattering By Aligned Non-spherical Particlesmentioning
confidence: 99%
“…Draine & Weingartner (1996) demonstrated the efficiency of radiative torques using numerical simulations, while Abbas et al (2004) demonstrated it in a laboratory setup. The radiative torque mechanism means the transfer of momentum by collisions of photons onto the grain, causing a torque which makes the grain rotate around its axis.…”
Section: Introductionmentioning
confidence: 99%